Sanskrit, Gāndhārī and Bactrian manuscripts in the Hirayama Collection - Tamai, Tatsushi (The International Research Institute for Advanced Buddhology, Soka University, 2016)
Sanskrit Dīrghāgama -- Sanskrit Saṃghāṭasūtra -- Sanskrit fragments -- Gāndhārī fragments -- Gāndhārī document -- Bactrian documents